PENGARUH LINGKUNGAN KELUARGA, DISPOSABLE INCOME, DAN PROMOSI TERHADAP MINAT MENABUNG DI BANK SYARIAH DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERASI - Azzahra, Amalia Rizka; Hakim, Luqman (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to determine the effect of family environment, disposable income, and promotion on interest in saving at Islamic banks, with religiosity as a moderating variable. This type of research is quantitative, with the research subjects being students of the Islamic Economics study program at state universities in Surabaya. The sampling technique used was simple random sampling. The data collection technique used was a questionnaire. The data analysis technique used was multiple linear regression analysis and moderate regression analysis (MRA) with SPSS 25 software. The results showed (1) family environment has an effect on interest in saving at Islamic banks; (2) disposable income has no effect on interest in saving at Islamic banks; (3) promotion has an effect on interest in saving at Islamic banks; (4) religiosity does not strengthen the effect of family environment on interest in saving at Islamic banks; (5) religiosity does not strengthen the effect of disposable income on interest in saving at Islamic banks; (6) religiosity does not strengthen the effect of promotion on interest in saving at Islamic banks.